2021
DOI: 10.12688/f1000research.53221.3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Surveillance of CTX-M-15-producing Klebsiella pneumoniae from the patients of a teaching hospital in Sindh, Pakistan.

Abstract: Background  The presence of Extended-spectrum β-lactamase positive bacteria in hospital setting is an aggravating influential factor for hospitalized patients, and its consequences may be hazardous. Therefore, there is a need for rapid detection methods for newly emerging drug-resistant bacteria. This study was aimed at the molecular characterization of Extended-spectrum β-lactamase -positive  Klebsiella pneumoniae isolates recovered from the patients of a teaching hospital in Sindh, Pakistan.   Methods  A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This increase was observed in urine samples, with a prevalence of 31.8–62.9%, and in pus samples, with a prevalence of 55.5% [ 30 ]. Several studies on ESBL‐producing Enterobacterales from various cities in Pakistan have reported findings similar to this study [ 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…This increase was observed in urine samples, with a prevalence of 31.8–62.9%, and in pus samples, with a prevalence of 55.5% [ 30 ]. Several studies on ESBL‐producing Enterobacterales from various cities in Pakistan have reported findings similar to this study [ 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…European Committee for Antimicrobial Susceptibility Testing (EUCAST) breaking points were used for Tigecycline (TGC) and Colistin susceptibility. 14 AST was done using different antimicrobial disks including Ampicillin (AMP) 10 μg, Gentamicin (CN) 10 μg, Ciprofloxacin (CIP) 5 μg, Levofloxacin (LEV) 5 μg, Amikacin (AK) 30 μg, Cotrimoxazole (SXT) 25 μg, Ceftriaxone (CRO) 30 μg, Ceftazidime (CAZ) 30 μg, Cefipime (FEP) 30 μg, Imipenem (IMP)10 μg, Merope-nem (MEM) 10 μg, Ampicillin+sulbactam (SAM) 20 μg, Piperacillin +Tazobactam (TZP) 110 μg, Coamoxiclav (AMC) 30 μg, Aztreonam (ATM) 30 μg, Minocycline (MIN) 30 μg, Doxycycline(DOX) 30 μg, Chloram-phenicol (CAP) 30 μg, Tigecycline (TGC) 15 μg. ATCC (American Type Culture Collection, Rockville, MD) of Escherichia coli was used for quality control of AST.…”
Section: Methodsmentioning
confidence: 99%
“…SHV-28, rsmA, aadA2, AAC(6')-Ib-cr6, eptB and gyrA were unique to JRCGR1 compared to the studied genomes, while CRP, eptB, EF-Tu and UhpT were shared with core genome. However CTX-M-15 and SHV-28 beta-lactamases, present in JRCGR1 (which render resistance to cephalosporins and work by antibiotic inactivation), have already been reported in some areas of Pakistan via PCR tests [35,36] or genome [37] not listed in the PATRIC database (from where we picked our data). S83I mutation in gyrA gene conferring resistance to ciprofloxacin has been previously detected in Pakistani isolates [38], which is common to global lineage.…”
Section: 4pan-genomicsmentioning
confidence: 99%